Two Projection Methods for Solving the Split Common Fixed Point Problem with Multiple Output Sets in Hilbert Spaces. (11th June 2021) - Kim, Jong Kyu; Tuyen, Truong Minh; Ha, Mai Thi Ngoc
Abstract: We study the split common fixed point problem with multiple output sets in Hilbert spaces. In order to solve this problem, we propose two new algorithms and establish two strong convergence theorems for both of them. Moreover, using these methods, we also remove the assumptions imposed on the norm of the transfer operators.